Search 75,806 tutors
FIND TUTORS
Ask a question
0 0

evaluate f(-3) when f(x)= 4x[sqr(3-x)]

Tutors, please sign in to answer this question.

2 Answers

Substitute (-3) into the equation
f(-3)=4(-3)(√3-(-3))
f(-3)=-12(√3+3)
ANSWER:
f(-3)=-12√6
 
√6 cannot be simplified, therefore it remains in the answer.
Hi Hannah;
If the equation is...
f(x)
we are evaluating x as x.
In this circumstance... 
we are evaluating x as -3.
Therefore...
f(x)= 4x[sqr(3-x)]
f(-3)=4(-3)[sqr(3--3)]
f(-3)=-12[sqr(6)]=-12(2.45)=-29